KEY POINTS OF THE ROAD SECURITY DEVELOPMENT CONCEPT - Иргашев Жавлонбек Гафурджанович; Жуманиёзов Нодирбек Ғиёс ўғли (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the main goal of the reforms implemented in the field of road traffic safety is to strengthen the legal guarantees of protecting the life and health of road users. In this regard, it was discussed the importance of developing new and modern mechanisms for ensuring road traffic safety, conducting scientific research in these areas of activity, and developing effective methods for investigating and solving problems.